Development of Web-Based Biology Learning Website on Sex Education to Improve Self-Regulation among EighthGrade Students - Tiara Anvadilla; Fredi Ganda Putra; Akbar Handoko (Jurnal Studi Multidisiplin Ilmu, 2026)
Purpose: This study set out to develop a web-based biology learning medium focused on sex education material, to measure how feasible that medium is, to capture how eighth-grade students respond to it, and to examine its influence on their selfregulation at SMP Negeri 36 Bandar Lampung.Methodology: The work used a research and development approach built on the Alessi and Trollip model, which moves through planning, design, and development stages. The finished product was validated by media, material, and language experts and was then tried out with twenty-nine eighth-grade students. Data came from validation sheets and response questionnaires and were analyzed with descriptive percentage techniques. Results: Media experts rated the product at 97%, language experts at 93.75%, and material experts at 92.45%, all falling in the very feasible category. Student responses reached 88 for the website itself and 97% for the sex education content, both very positive, while self-regulation averaged 78.4%, a good level. Conclusions: The website is feasible and workable as an independent learning medium that supports self-regulation. Limitations: The trial involved only one small class, so the results cannot yet be generalized.Contributions: The study gives schools a trustworthy digital option for teaching sensitive reproductive health topics.